Experiencing Digital Storytelling: Students’ Perception - Ahada, Ichi; Wardani, Ida; Rizki, Sanova; Izzatul Jannah, Ajeng (Educational Studies: Conference Series, 2024)
To foster global connections by promoting networking and collaboration through storytelling is the aim of this investigation, beginning with students in a classroom setting who will collaboratively write a story by merging their ideas and creativity. The primary activities involve reading, writing, and sharing, where participants read a paragraph, add to it, and share their contributions with others. The research focuses on understanding students' perceptions of their experiences with digital storytelling. Engaging students in meaningful learning experiences through digital storytelling is an effective strategy that enhances teamwork, creativity, and writing skills. The integration of technology makes the storytelling process more engaging and enjoyable for students. Findings indicate that students have a positive view of digital storytelling as it stimulates their imagination, encourages collaboration, and improves their writing abilities